Construction of a middle-range nursing theory for transpersonal home care - Luana Tonin; Maria Ribeiro Lacerda; Paula Manuela Jorge Diogo; Marcos Antônio Gomes Brandão; Marilene Loewen Wall; Paulo Roberto Lima Falcão do Vale (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objectives: to describe the development of a middle-range nursing theory for transpersonal home care. Methods: this is a theoretical study that used concept analysis, statement synthesis and derivation. It combined theoretical deduction strategies with induction, based on literature review and concept analysis. Results: the central concept was derived from Jean Watson’s Unitary Care Science theoretical framework. The synthesis of the statements between the concepts led to the elaboration of a middle-range theory. Fourteen assumptions and ten propositions were constructed, in addition to a diagram representing the middle-range theory. Final Considerations: the constructed theory is intended to contribute to home care, covering physiological, psychological, sociocultural, developmental and spiritual needs. Theoretical and empirical validation is suggested to confirm, refute or renew the theory concepts, assumptions and propositions.